2D MXene-Based Materials for Electrocatalysis - Liu, Jiapeng; Peng, Wenchao; Li, Yang; Zhang, Fengbao; Fan, Xiaobin (Transactions of Tianjin University, 2020)
MXenes, as an emerging 2D material, are expected to exert a great influence on future energy storage and conversion technologies. In this review, we systematically summarize recent advances in MXene-based materials in electrocatalysis, particularly in the hydrogen evolution, oxygen evolution, oxygen reduction, nitrogen reduction, and CO 2 reduction reactions. Crucial factors influencing the properties of these materials, such as functional groups, conductivity, and interface, are discussed, and challenges to the future development of MXene-based electrocatalysts are presented.